Modeling The Kinetics of Lactic Initiators Using Lactobacillus Delbrueckii Ssp Bulgaricus and Streptococcus Thermophilus in Jora Corn Germinated Grain Hydrolysate - Zárate-Sarapura, E.; Sotelo-Méndez, A.; Cáceres-Paredes, J.; Vigo-Ingar, K.; García-Flores, S.; Valdivia-Zuta, J.; Solís-Farfán, R.E; Miranda, B.C.L. Montaño (International Journal of Membrane Science and Technology, 2023)
The objective of this research was to determine the growth kinetics of lactic acid starter bacteria such as Lactobacillus delbrueckii ssp bulgaricus and Streptococcus thermophilus, experimentally using the Gompertz and Baranyi-Roberts mathematical models. As part of the method, lactic bacteria were inoculated in a germinated jora maize hydrolyzate at temperatures of 40°C, 41°C and 42°C. The Log10 CFU/ml growth initiators will be finished, for 12 hours with iterations of 1 hour each. The growth parameters and lactic initiated strains were adjusted with the Gompertz and Baranyi-Roberts models using the Curveexpert 1.4 and DMfit programs from Combase, which were validated through the mathematical indices R2, root mean square error (RMSE), bias factor (Bf) and precision (Af). The results showed that increasing temperatures decreased with lag time, while generation time slightly increased growth velocity based on logarithmic levels of the initial population. The adjustment of the kinetic growth curves showed that the initial population (N0) for the Gompertz model at temperatures of 40°C, 41°C and 42°C are 5.28, 5.46 and 5.36 Log CFU/ml, with no significant difference between them (p> 0.05), it will increase the logarithmic growth levels of 2.0, 2.37, 2.99 Log CFU/ml, with µmax speeds of 0.53, 0.49 and 0.45 Log CFU/ml/h and for the Baranyi-Roberts model the initial population at the same temperatures. of study are 5.25, 5.39 and 5.37 Log CFU/ml, with logarithmic levels of 1.93, 2.46, 3.02 Log CFU/ml and µmax growth rates of 0.33, 0.36 and 0.48 Log CFU/ml/h corresponding to Lbd.